Effective group discussion : - Galanes, Gloria J. (McGraw-Hill, 2007)
Combining the most recent research findings with practical tools students need to become productive group members, this leading text covers secondary groups of all kinds: work groups, committees, task forces, self-directed work teams, and other small groups whose objectives include finding solutions to problems, producing goods, and creating policies. In this edition, the authors have expanded coverage of computer-mediated communication and updated relevant information about diversity and culture in chapter 5 and throughout the text.